The School Strategies in Implementing Anti-Bullying Education and Student Protection - Maulida, Tasya; Alam, Naufal Ahmad Rijalul (Fakultas Tarbiyah dan Ilmu Keguruan (FTIK) UIN Sayyid Ali Rahmatullah Tulungagung, 2025)
Purpose – This research explores the role of schools in implementing anti-bullying education and student protection at SDN 001 Rantau, Rokan Hilir. The phenomenon of bullying in the school environment, both verbal and non-verbal, often hurts students' mental health, sense of security, and learning motivation. Methods – This study employed a descriptive qualitative approach, using in-depth interviews with the principal and teachers, direct observation, and students as the main informants, with documentation serving as supporting data. The results showed that the school had implemented various strategies, including the formation of a special team to prevent bullying. Findings – The results showed that the school had implemented various strategies, including the formation of a special team to prevent bullying. The implementation of anti-bullying programs through learning activities, and cooperation with external parties such as the health department and the police. In addition, the programs such as anti-bullying chants and claps, as well as the implementation of the Pancasila Student Profile Strengthening Project (P5), have proven effective in instilling positive values and creating an inclusive school culture. Limitations – This research is limited to literature studies and field data obtained from a single school context. Value – This study recommends strengthening anti-bullying policies through deeper curriculum integration, enhanced teacher training, and increased parental involvement to foster a safer and more supportive educational environment for students.